Topical application of daphnetin hydrogel for traumatic brain injury - Ma, Yuanhao; Liu, Yu; Guo, Jianqiang; Chen, Zhongjun; Zhao, Zongren; Zheng, Jinyu (Frontiers in Neuroscience, 2024)
Background: Traumatic brain injury (TBI) causes neuronal cell damage and dysfunction. According to previous studies, daphnetin (Dap) has a protective effect in neurological injury. However, the in vivo bioavailability of daphnetin is not high. The purpose of this study was to determine whether administering daphnetin directly into the site of injury via a hydrogel drug carrier could improve its therapeutic impact. Methods: Tripolycerol monostearates / daphnetin (TM/Dap) hydrogels were prepared and characterised using water bath heating, scanning electron microscopy (SEM) and small animal in vivo imaging techniques. The TBI model was established using the Feeney free fall impact method. Using the Morris water maze test, the mNSS neurological deficit rating scale, haematoxylin-eosin staining, and liver and kidney function tests, the therapeutic benefit of TM/Dap and its toxic side effects were assessed. The therapeutic effects of TM/Dap were further investigated using wet and dry gravimetric methods, Evans blue staining, protein immunoblotting, immunofluorescence staining techniques and ELISA. Results: The efficacy of the TM/Dap hydrogel in gradually releasing daphnetin in the context of traumatic brain damage was shown by both in vitro and in vivo tests. Behavioural experiments showed that the learning and spatial memory abilities of TM/Dap hydrogel treated mice were significantly improved in the water maze experiment. And TM/Dap hydrogel has high biosafety for organisms. The results of the therapeutic mechanism of action showed that TM/Dap hydrogel showed more significant efficacy in reducing the neuroinflammatory response caused by TNF-α, IL-6 and other factors, as well as promoting the recovery of post-traumatic neurological function. Conclusions: The use of hydrogel as a drug carrier for daphnetin showed more significant efficacy in reducing neuroinflammatory response, protecting nerve tissue and promoting post-traumatic neurological recovery compared with traditional drug delivery methods.